2013
DOI: 10.1071/sh12067
|View full text |Cite
|
Sign up to set email alerts
|

Medical male circumcision and HIV risk: perceptions of women in a higher learning institution in KwaZulu-Natal, South Africa

Abstract: Background Medical male circumcision (MMC) reduces the risk of HIV acquisition for men in heterosexual encounters by 50–60%. However, there is no evidence that a circumcised man with HIV poses any less risk of infecting his female partner than an uncircumcised man. There may be an additional risk of HIV transmission to female partners during the 6-week healing period and if condoms are used less often after circumcision. The aim was to explore young women’s perspectives on MMC, with a view to developing clear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…These results confirm that women should be involved in the efforts to recruit men for VMMC, as female perception of circumcision may be significantly influential in a man’s decision to undergo MC [7,17,25]. This involvement, however, is not necessarily feasible throughout Eastern and Southern Africa due to cultural resistance, in particular among health providers, such as described in Malawi [26].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…These results confirm that women should be involved in the efforts to recruit men for VMMC, as female perception of circumcision may be significantly influential in a man’s decision to undergo MC [7,17,25]. This involvement, however, is not necessarily feasible throughout Eastern and Southern Africa due to cultural resistance, in particular among health providers, such as described in Malawi [26].…”
Section: Discussionmentioning
confidence: 55%
“…In Kenya, as shown by a community-based survey, factors affecting opinion included a belief that circumcision was not part of the local culture, the perception of a long healing period following the procedure, the lack of a specific motivation to seek out services, and the general fear of pain associated with the circumcision procedure and healing process [23]. Finally, misinformation regarding the association of MC and HIV risk has been revealed in qualitative studies conducted in Tanzania [24] and South Africa [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Other concerning knowledge gaps identified included that almost half of women reported that a woman is protected from HIV if her partner is circumcised. This dangerous myth has been reported in qualitative studies in the Western Cape and Tanazania (8789). Interestingly, a study with university students in KwaZulu-Natal did not observe the same mis-information suggesting that education may overcome this misperception (89).…”
Section: Discussionmentioning
confidence: 56%
“…This dangerous myth has been reported in qualitative studies in the Western Cape and Tanazania (8789). Interestingly, a study with university students in KwaZulu-Natal did not observe the same mis-information suggesting that education may overcome this misperception (89). Participants also demonstrated low knowledge of safer conception strategies such as sperm washing, timing sex to peak fertility, manual insemination, and treatment as prevention, thus explaining infrequent safer conception practices.…”
Section: Discussionmentioning
confidence: 56%
“…There is concern that women do not directly benefit from medical male circumcision (Baeten et al, 2009; Mantell et al, 2013). In this study, some healthcare providers erroneously believed that medical male circumcision would be protective for women, and some had concerns that women clients may engage in more risky behavior.…”
Section: Discussionmentioning
confidence: 99%